Second Five year Plan 1956-61 (Community Project Schemes) Himachal Pradesh - Planning Commission (Planning Commission, 1956)
However, schemes nos. 17 to 30 are those schemes which have been prepared for tribal areas. These schemes are expensive schemes (lying very much into the interior and at higher altitudes requiring heavy blasting work), costing to Rs. 39.7 lacs for 6750 acres. They have been proposed to be executed from funds exclusively for tribal areas. In such a case the schemes left are from 1 to 16 which for 22505 acres cost Rs. 66.87 lacs only out of which Rs. 46 lacs are required for the II-Five Year Plan period. The provision for Major kuhls under G.M.F. is Rs. 62.4 (for 20800 acres).
Himachal Pradesh Government